Corporate University: Strategic Tool For Talent Management Development And talent Retention - Prastika, Netty Dyan; Rahmah, Dian Dwi Nur; Rasyid, Miranti; Solita, Fara Ayu; Nurdin, Nurafifah (MOTIVA: JURNAL PSIKOLOGI, 2025)
Human resources are the key to an organization's success. Individual competencies serve as the fuel for achieving organizational effectiveness. A corporate university can be an effective tool for achieving organizational goals, particularly in talent management development and enhancing talent retention. This study aims to explore the role of a corporate university as a strategic tool in developing talent management and retention to improve organizational performance at KDOD LAN Samarinda. Using a quantitative approach, the study involved 46 employees of Puslatbang KDOD LAN Samarinda, who have implemented the corporate university model. The analysis results indicate that talent management (β = 0.509; p < 0.001) and talent retention (β = 0.436; p < 0.001) have significant effects on organizational performance. The combined contribution of these variables to organizational performance reaches 77.6% (R² = 0.776). These findings affirm that a corporate university is an effective strategic tool for integrating talent management with organizational strategic objectives, creating a supportive environment for continuous learning, and enhancing organizational competitive advantage